Meningkatkan Rasa Kepercayaan Diri pada Peserta Didik melalui Konseling Kelompok di Sekolah - Dania Hasanah; Suci Dinaria; Aida Safitri; Graciella Lumban Gaol; Ratna Sari Dewi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to evaluate how effective group counseling is in developing students' self-confidence, as well as identifying various techniques that can be used in the process in the school environment. The research method uses a literature review, which focuses mainly on the analysis of various library sources. The results of the review found that group counseling has indeed been proven to be able to develop students' self-confidence. There are various techniques that can be applied in group counseling sessions to support the development of students' self-confidence, such as Cognitive Behavior Therapy (CBT), Self-Instruction, Rational Emotive Behavior Therapy (REBT), Group Discussion, Cognitive Restructuring, Self Talk, Cinema Therapy, Experiential Learning, and the Client Centered approach. The application of these techniques in group counseling sessions is believed to be able to help students in forming and strengthening their self-confidence.